Constructing a Pentahelix Model for IAD Implementation in Social Forestry-Based Sustainable Development in Lumajang Regency - Wulan Andari, Retno; Khusaini, Moh.; Hakim, Luchman; Sukoharsono, Eko Ganis (Indonesian Green Technology Journal, 2026)
Sustainable development based on natural resources requires collaborative governance capable of harmonizing social, economic, and environmental dimensions, particularly in the implementation of social forestry, which continues to face institutional and actor coordination challenges. This study aims to construct a pentahelix model for the implementation of Integrated Area Development (IAD) based on social forestry to support sustainable development in Lumajang Regency. The research employed a qualitative approach with a case study design conducted in the social forestry IAD development areas of Senduro and Pasrujambe Districts. Data were collected through in-depth interviews, field observations, and document analysis involving key stakeholders, including government, academics, industry/UMKM, communities, and financial institutions/cooperatives, and were analyzed using descriptive qualitative methods. The findings indicate that local actors have a relatively strong understanding of the IAD concept, community participation is high, and positive impacts are observed across economic, social, and environmental aspects in line with the achievement of the Sustainable Development Goals. The discussion highlights that the community serves as the core actor, supported by synergistic roles of other actors, enabling the constructed Pentahelix–IAD Model to function as a contextual, collaborative, and sustainable operational framework at the regency level.